Asthma - From Childhood Asthma to ACOS Phenotypes 2016
DOI: 10.5772/63651
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Allergic Asthma and Current Perspectives on Therapeutic Management

Abstract: Globally, more than 300 million people are asthmatics and this number has been estimated to become 400 million by 2025. Asthma is a chronic inflammatory condition, which, although has no cure, is treatable in most patients. The most common structural alterations in asthmatic airways include thickening of the epithelial and sub epithelial layers, increased airway smooth muscle mass, and angiogenesis. Several genetically controlled factors greatly influence the predisposition and severity of allergic asthma. Twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 196 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…Exposure to allergens causes an immediate hypersensitivity reaction characterized by elevated allergen-specific IgE production [ 1 , 2 ]. More than 300 million people are affected worldwide, and studies predict that by 2025, it will reach 400 million [ 3 ]. Most recent statistics reported that asthma has claimed 417,918 lives globally resulting in 24.8 million disability-adjusted life years (DALYs) affecting around 15% to 20% of people in developed countries whereas 2% to 4% in less developed countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to allergens causes an immediate hypersensitivity reaction characterized by elevated allergen-specific IgE production [ 1 , 2 ]. More than 300 million people are affected worldwide, and studies predict that by 2025, it will reach 400 million [ 3 ]. Most recent statistics reported that asthma has claimed 417,918 lives globally resulting in 24.8 million disability-adjusted life years (DALYs) affecting around 15% to 20% of people in developed countries whereas 2% to 4% in less developed countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent statistics reported that asthma has claimed 417,918 lives globally resulting in 24.8 million disability-adjusted life years (DALYs) affecting around 15% to 20% of people in developed countries whereas 2% to 4% in less developed countries [ 4 , 5 ]. Allergic asthma is associated with genetic predisposition, as shown by twin studies which reported that 60% to 70% of asthma cases are caused by genetics, and asthma heritability was estimated to range from 55% to 74% in adults and 90% in children [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…allergic rhinitis, type 1 diabetes, primary biliary cirrhosis, rheumatoid arthritis, ulcerative colitis, Crohn's disease, and ankylosing spondylitis. Fenretinide (FEN), a vitamin A derivative, corrects the aberrant inflammatory responses and improves lung functions in both cystic fibrosis (CF) (Garić et al 2017;Guilbault et al 2008Guilbault et al , 2009Youssef et al 2016) and allergic asthma (Kanagaratham et al 2014). In CF, our lab has shown that Fenretinide improves the lung function by elevating the levels of VLCCs and lowering the levels of LCCs (Garić 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Asthma is a heterogeneous disease with different inflammatory and immunologic phenotypes, and these phenotypic diversity affected the therapeutic outcomes of the different treatment approaches. [30] Additionally, gene and environment gene interaction may ameliorate therapeutic response [31] Responses to current asthma therapies varies greatly, which is probably related to the inter-patients differences in pathogenesis. [32] Thus due to several phenotypes, subtypes, and asthma endotypes, this study was conducted to determine the role of interleukin 5 as asthmatic biomarker in Iraqi community in order to target the trait.…”
Section: Introductionmentioning
confidence: 99%